Child abuse materials as digital goods: Why we should fear new commercial forms - Kemal Veli Acar (Kiel Institute for the World Economy (IfW), 2017)
Psycho-sociological and legal aspects of online child sexual abuse such as criminalization, offender profiling, and rehabilitation have been thoroughly studied in the literature. The economics of the issue may appear relatively insignificant at first sight, considering the devastating effects on victims. However, understanding the child abuse materials' economic value better is crucial for developing more effective crime prevention strategies particularly for emerging threats, since the disruption of an illicit market is closely related to the perceived value of such materials. Even for relatively traditional methods like membership-only commercial websites, law enforcement responses do not appear to recognize the economic facts of child abuse materials as digital goods. Similar to the legal actions taken against conventional forms of crime, law enforcement agencies preferred to take down the markets of such materials. Thus, they diminished the demand and supply of child abuse materials by shutting down online platforms and apprehending the abusers. However, in line with technological advances, new ways of offending have emerged that make these measures almost useless. Specific characteristics and dangers of these emerging threats from an economic perspective seem underestimated or completely ignored. This paper aims to analyze the economic aspect of online child abuse materials as a type of digital goods, and it discusses how new forms of commercial sexual exploitation such as crowdfunding and webcam child prostitution challenge the widely accepted policies on the fight against online child sexual abuse.
Keywords: A10; K42; 330; online child sexual abuse; commercial sexual exploitation; child abuse materials; crime prevention; policy making; crowdfunding; webcam child prostitution